Sustainability of Poultry Farm By Adopting Improved Farm Management Practices of Poultry Farmers In Namakkal District - P. Ranjithkumar and Dr. C. Gunasekaran (International journal of economic perspectives, 2022)
Agriculture and allied activities provides employment opportunities directly or indirectly to 2/4 of Indian population. The poultry industries are one among in the agri-allied sector which is contributing Rs. 7,500 crores to the nation GDP. In these industries, more than 2.5 million peoples are working, they are mostly from rural area. The sustainability of the poultry farm industries depends upon economic, environmental, social and management aspects. The present paper attempts to analyse the economic status of the poultry farmers, their improved management practice towards various types of poultry, investment pattern in poultry farm assets, farmers personal factors, housing of poultry, so on. The researcher has suitably linked these aspects towards poultry farm sustainability and development in the context of improved management practices adopted in poultry production. The statistical tools, percentage analysis, chi-square analysis, average rank analysis have been employed to analysis the data collected from 184 sample poultry farmers in the study area of Nammakkal district. The conclusion drawn based on the finding of the study, which would helpful to the improvement of poultry farm industry, income of the poultry farmers.